RNA-Mediated Reciprocal Regulation between Two Bacterial Operons Is RNase III Dependent - Christopher M. Johnson (American Society for Microbiology, 2011)
ABSTRACT In bacteria, RNAs regulate gene expression and function via several mechanisms. An RNA may pair with complementary sequences in a target RNA to impact transcription, translation, or degradation of the target. Control of conjugation of pCF10, a pheromone response plasmid of Enterococcus faecalis, is a well-characterized system that serves as a model for the regulation of gene expression in bacteria by intercellular signaling. The prgQ operon, whose products mediate conjugation, is negatively regulated by two products of the prgX operon, Anti-Q, a small RNA, and PrgX, the transcriptional repressor of the prgQ promoter. Here we show that Qs, an RNA from the 5′ end of the prgQ operon, represses expression of PrgX by targeting prgX mRNA for cleavage by RNase III. Our results demonstrate that the prgQ and prgX operons each use RNAs to negatively regulate gene expression from the opposing operon by different mechanisms. Such reciprocal regulation between two operons using RNAs has not been previously demonstrated. Furthermore, these results show that Qs is an unusually versatile RNA, serving three separate functions in the regulation of conjugation. Understanding the potential versatility of RNAs and their various roles in gene regulatory networks will allow us to better understand how cells regulate complex behavior. IMPORTANCE Bacteria use RNA to regulate gene expression by a variety of mechanisms. The prgQ and prgX operons of pCF10, a conjugative plasmid of Enterococcus faecalis, have been shown to negatively regulate one another by a variety of mechanisms. One of these mechanisms involves Anti-Q, a small RNA from the prgX operon that prevents gene expression from the prgQ operon. In this work, we find that Qs, an RNA from the prgQ operon, negatively regulates gene expression from the prgX operon. These findings have a number of implications. (i) The Anti-Q and Qs RNAs act by different mechanisms, highlighting the variety of ways in which bacteria can regulate gene expression using RNAs. (ii) Reciprocal regulation between operons mediated by small RNAs has not been previously described, deepening our understanding of how bacteria regulate complex behavior. (iii) Additional roles for Qs have been described, demonstrating the versatility of this RNA.